2015
DOI: 10.1111/ajt.13011
|View full text |Cite
|
Sign up to set email alerts
|

List and Liver Transplant Survival According to Waiting Time in Patients With Hepatocellular Carcinoma

Abstract: The time that patients with hepatocellular carcinoma (HCC) can safely remain on the waiting list for liver transplantation (LT) is unknown. We investigated whether waiting time on the list impacts transplant survival of HCC candidates and transplant recipients. This is a single-center retrospective study of 283 adults with HCC. Patients were divided in groups according to waiting-list time. The main endpoint was survival. The median waiting time for LT was 4.9 months. The dropout rates at 3-, 6-, and 12-months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
2
16
1
2
Order By: Relevance
“…This perspective is important from the patient's point of view and in understanding effectiveness because the time spent on the WL tends to exclude patients with unfavorable tumor biology who tend to have tumor progression that disqualifies them while waiting. (31,32) Our data support this premise as the dropout rates were significantly higher in patients with M1 tumors, even with the relatively short wait times as found in our patient population (median time to transplant 5 4.2 months).…”
Section: Discussionsupporting
confidence: 82%
“…This perspective is important from the patient's point of view and in understanding effectiveness because the time spent on the WL tends to exclude patients with unfavorable tumor biology who tend to have tumor progression that disqualifies them while waiting. (31,32) Our data support this premise as the dropout rates were significantly higher in patients with M1 tumors, even with the relatively short wait times as found in our patient population (median time to transplant 5 4.2 months).…”
Section: Discussionsupporting
confidence: 82%
“…Finally, we have not yet validated the wait time “sweet spot”. A single-center study attempted to identify the “optimal” wait time for LT in HCC patients using an intention-to-treat survival analysis 38 , but we are concerned about the statistical bias as wait time itself is part of the observation. For example, a patient must survive 6 months from HCC diagnosis to be in the 6–18-month wait time group and patients dying within 3 months of diagnosis would automatically be included in the <3-month wait time group.…”
Section: Discussionmentioning
confidence: 99%
“…These patients can be treated immediately. In addition, approximately 5 to 25% of those added to an organ transplant waiting list for HCC were removed from the list within a year (18). In these patients, although they were originally suitable to be organ recipients, HCC progressed swiftly despite bridging therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the survival rates of patients who received liver transplant particularly quickly were worse than those of patients who survived for 6 to 12 months of bridging therapy. Multivariate analysis showed no adverse effect for a longer waiting time (18). Some publications even found that waiting time could be used as an important selection criterion (known as the "test of time") (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%